The Mayflower House
This is the Armco-Ferro Porcelain Enamel Frameless Steel House with its little guest cottage snuggling as cozy as can be, to take care of family overflow either temporary or permanent. The attractive porcelain enamel steel walls never need paint and are as easy to keep clean as a china dish. It's a great idea and the cost is very reasonable. This house is called "The Mayflower House" because it is decorated by Mayflower Wallpapers.